Code choice in Egyptian TV advertisements - Younes, Mostafa (AUC Knowledge Fountain, 2017)
This study examines the code choice made by content producers in Egyptian television (TV) advertisements. We consider the emergence of new types of TV networks, advertised products, services and messages conveyed in TV advertisements. These TV channels have raised competition in marketing and advertising where it is possible to see content producers choosing their language carefully to specifically target people from different social backgrounds. This study employs a qualitative analysis design with some frequency count to demonstrate the language varieties that are used in TV advertisements. Badawi’s 1973 model is used as a framework of analysis, where he proposed a continuum of five levels of Arabic. The data in this study consists of 220 Egyptian advertisements taken from YouTube and which had previously appeared on broadly two types of Egyptian TV channels: type one, the popular TV networks; and type two, the specialty channels watched by more of the uneducated classes. The findings in this study show a high frequency use of the colloquial of enlightened in type one TV advertisements, while the colloquial of illiterates has similar frequency in type two TV advertisements. The code choice is determined by: the addressees’ social class and age, the nature of the advertised products, the presented image of the actor component and the desired effect’s meaning. Based on the researcher’s analysis there is an increased use of diglossic code mixing where the Colloquial varieties are dominant and the MSA is an embodied variety. The investigated functions of code switching are; convince and persuade those determine the code choice and requires several linguistic and stylistic techniques to reach the utmost effect.